2011
DOI: 10.1152/physiolgenomics.00145.2010
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs 29 are involved in the improvement of ventricular compliance promoted by aerobic exercise training in rats

Abstract: MiRNAs regulate cardiac development, hypertrophy, and angiogenesis, but their role in cardiac hypertrophy (CH) induced by aerobic training has not previously been studied. Aerobic training promotes physiological CH preserving cardiac function. This study assessed involvement of miRNAs-29 in CH of trained rats. Female Wistar rats (n ϭ 7/group) were randomized into three groups: sedentary (S), training 1 (T1), training 2 (T2). T1: swimming sessions of 60 min/5 days/wk/10 wk. T2: similar to T1 until 8th wk. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
132
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 39 publications
7
132
1
10
Order By: Relevance
“…In contrast, pathological cardiac hypertrophy did not activate the Akt signal cascade and in some cases the absence of Akt1 profoundly exacerbated the transverse aortic constriction or endothelin 1-stimulated pathological cardiac hypertrophic, suggesting that the Akt activation pathway may differentiate between physiological and pathological hypertrophy (44,45). Accordingly, we observed that the swimming training protocols increased the cardiac phosphoSer 473 -Akt protein expression, indicating its participation in physiological cardiac hypertrophy (20). Therefore, in a recent study we showed that a session of strength exercise consisting of 4 sets of 12 repetitions with an 80% work overload promoted increased Akt activity in a group exercised and killed 30 min after the strength training session.…”
Section: Exercise-induced Cardiac Hypertrophy Via At1 Receptormentioning
confidence: 58%
See 4 more Smart Citations
“…In contrast, pathological cardiac hypertrophy did not activate the Akt signal cascade and in some cases the absence of Akt1 profoundly exacerbated the transverse aortic constriction or endothelin 1-stimulated pathological cardiac hypertrophic, suggesting that the Akt activation pathway may differentiate between physiological and pathological hypertrophy (44,45). Accordingly, we observed that the swimming training protocols increased the cardiac phosphoSer 473 -Akt protein expression, indicating its participation in physiological cardiac hypertrophy (20). Therefore, in a recent study we showed that a session of strength exercise consisting of 4 sets of 12 repetitions with an 80% work overload promoted increased Akt activity in a group exercised and killed 30 min after the strength training session.…”
Section: Exercise-induced Cardiac Hypertrophy Via At1 Receptormentioning
confidence: 58%
“…Our results showed that the first swimming training protocol did not modify the gene expression of ANF, skeletal α-actin or α/β-MHC, whereas the second training protocol significantly reduced the left ventricle levels of skeletal α-actin by 53% and increased the left ventricle levels of α/β-MHC by 98% (20). α-MHC has been associated with increased myosin ATPase activity and enhancement of contractility, corroborating the improvement of ventricular function observed with aerobic training (21).…”
Section: Eccentric Cardiac Hypertrophy Induced By Endurance Trainingmentioning
confidence: 60%
See 3 more Smart Citations